Belgium : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2013)
This financial stability assessment provides an update on the significant regulatory and supervisory developments in the banking and insurance sectors of Belgium since 2006. The Belgian financial system is relatively large with solid capital buffers on aggregate, and the 2008 global financial crisis has had a major impact on the Belgian financial sector. The links between banks and the Belgian sovereign have intensified owing to the crisis, with total exposure of the banking sector to the federal government at 10 percent of banking sector assets in mid-2012.